Penerapan Deret Fourier Pada Sistem Pendengaran Manusia - Tri Widjajanti (FMIPA Universitas Papua, 2006)
Natural vane voices comes to the humaneary on the Forier Series P(t), while the human earing system only accepts the wore of voices on the Fourier Series berhingga Q (t). The different between Fories Series P(t) and Q(l) can be eliminase using. Approximation Quadrate Smallest Method.. Therefore q(t) is a result of natural vane approach.